Effect of Tooth Preparation Design on Fracture Resistance and Marginal Adaptation of Zirconia-Reinforced Lithium Silicate and 3D-Printed Overlays - Tartuk, Bulent Kadir; Altintas, Eyyup; Akgul, Mustafa Caner (Mdpi, 2026)
Overlay restorations offer a conservative solution for teeth with substantial loss of tooth structure, but their success depends largely on the preparation design, material type, and fabrication technique. This study aimed to assess the effects of two different preparation designs and fabrication techniques on the fracture resistance and marginal adaptation of overlays fabricated from zirconia-reinforced lithium silicate (ZLS) and 3D-printed resin. Forty extracted human molars were randomly divided into two preparation design groups: occlusal reduction (O) and occlusal reduction with a round shoulder (OS). Each group was subdivided based on the material type: ZLS or 3D-printed resin (n = 10 per subgroup). Restorations were designed using CAD and manufactured using milling (ZLS) or additive manufacturing (3D-Printed). After cementation and thermomechanical aging (5500 cycles, 5-50 degrees C), marginal gaps were measured at 20 predefined points using scanning electron microscopy (SEM). The fracture resistance was tested using a universal testing machine. Data were analyzed using two-way ANOVA and post hoc tests (alpha = 0.05). The preparation design had a significant effect on both fracture resistance and marginal adaptation (p < 0.05). Group O showed significantly smaller marginal gaps than Group OS for both materials. The ZLS overlays exhibited a significantly higher fracture resistance than the 3D-printed resin overlays. All groups demonstrated marginal gaps within the clinically acceptable range (<120 mu m). The fracture resistance and marginal adaptation of overlay restorations are significantly influenced by the preparation design and material type. A simpler occlusal reduction design results in better marginal adaptation, whereas round shoulder preparations provide a higher fracture resistance. Although the 3D-printed resin showed lower fracture resistance, its marginal adaptation was comparable to that of milled restorations, suggesting its potential as a conservative and cost-effective polymer composite alternative for digitally fabricated overlay restorations.
Keywords: overlay restoration; preparation design; fracture resistance; marginal fit; 3D printing; additive manufacturing; zirconia-reinforced lithium silicate; CAD/CAM